A simple synthesis of urchin-like Pt-Ni bimetallic nanostructures as enhanced electrocatalysts for the oxygen reduction reaction - Choi, Kwang-Hyun; Jang, Youngjin; Chung, Dong Young; Seo, Pilseon; Jun, Samuel Woojoo; Lee, Ji Eun; Oh, Myoung Hwan; Shokouhimehr, Mohammadreza; Jung, Namgee; Yoo, Sung Jong; Sung, Yung-Eun; Hyeon, Taeghwan (ROYAL SOC CHEMISTRY, 2016)
The synthesis of urchin-like Pt-Ni bimetallic nanostructures is achieved by a controlled one-pot synthesis. Pt-Ni nanostructures have superior oxygen reduction reaction activities in both with and without specific anion adsorption electrolytes due to the geometric and alloying effects.
Keywords: SINGLE-CRYSTAL SURFACES; UNDERPOTENTIAL DEPOSITION; NANOPARTICLES; MONODISPERSE; NANOCRYSTALS; NANOCATALYSTS; CHEMISTRY; CATALYSIS